Reconfiguring Local Leadership: Legal Policy Analysis of Village Head Term Extension under Law No. 3 of 2024 - Wasil Wasil (Rechtenstudent, 2024)
The term of office of the village head is already long, there is still dissatisfaction expressed by the village head. The Indonesian Village Government Association and the Indonesian Village Apparatus Association (PPDI) have extended the term of office of the village head to 9 years per period for 3 periods. The demand for an extension of the term of office of the village head is based on several reasons, one of which is the need for stable and sustainable leadership. In some cases, village heads who have experience and in-depth knowledge of local conditions are considered capable of leading the village more effectively, especially in facing complex challenges. So that in the latest Law, namely Law Number 3 of 2024, the term of office of the village head was changed to eight years with two terms. Thus, the focus of this research is how the legal policy is regarding the addition of the term of office of the village head in Law Number 3 of 2024 concerning Villages. With the type of library research with primary legal materials, namely Laws, while secondary legal materials are books regarding the addition of the term of office of the Village Head. The results of this study indicate that the current term of office and period of the village head are considered insufficient to develop the village due to tension and polarization of society after the village head election, the term of office of the village head is too short will cause failure to achieve the vision and mission. The addition of a long term of office for the village head does not guarantee that a development climate will be built.